Development of savonius and darrieus vertical axis hybrid wind turbine to increase effectiveness in wind energy conversion system - Nurul Razliana Abd Razak (School of Electrical System Engineering, University Malaysia Perlis, 2013)
This thesis presents the investigation of the potential of wind energy in Perlis and the development of Savonius and Darreius Vertical Axis Hybrid Wind Turbine for the low wind speed application (below 2 m/s). The objectives of this research are to investigate the potential of wind energy based on the weather data in Kangar, Perlis.